Zoonoses in the workplace: A Seroprevalence study of Coxiella, Brucella, and Leptospira among marine mammal rescue and rehabilitation workers in California - Adam Bjork; Robyn A. Stoddard; Alicia D. Anderson; Marie A. dePerio; Richard Todd Niemeier; Joshua S. Self; Kelly A. Fitzpatrick; Frances M. D. Gulland; Cara L. Field; Gilbert J. Kersh; John D. Gibbins (Wiley, 2024)
Abstract Background Q fever, brucellosis, and leptospirosis are zoonoses typically associated with terrestrial animal reservoirs. These bacterial agents are now known to infect marine mammal species, though little is known about potential human health risks from marine mammal reservoir species. We investigated potential risks of these bacteria in humans associated with marine mammal exposure. Methods The Marine Mammal Center (TMMC) in Sausalito, California, requested a Health Hazard Evaluation by the National Institute for Occupational Safety and Health. In June 2011, an investigation occurred, which included a written questionnaire and serosurvey among workers for Coxiella burnetii, Brucella spp., and Leptospira spp., and an environmental assessment for C. burnetii. Results Serologic evidence of past exposure was detected in 4% (C. burnetii), 0% (Brucella), and 1% (Leptospira) of 213 participants, respectively. One of 130 environmental samples tested positive for C. burnetii. No significant marine mammal‐specific risk factors were identified, but some safety deficiencies were noted that could lead to a higher risk of exposure to zoonotic diseases. Conclusion Although this study did not identify disease exposure risks associated with marine mammals, additional studies in different settings of other groups with frequent exposure to marine mammals are warranted. Some deficiencies in safety were noted, and based on these, TMMC modified protocols to improve safety.